Development of universal transport shceme for road traﬃc optimization in urban conditions. - V. D. Timokhovets; Ya. I. Chichilanova (Вестник СибАДИ)
Introduction. This article addresses the issue of optimizing the movement of road users in an urban environment. The need to resolve this issue arose due to the suboptimal design of the city’s street-road network, consisting in an increase in traﬃc intensity to limit values and the inability of traﬃc lights to solve the problems of global demand for vehicle movement. It is also important to address the issue of the movement of ever-increasing pedestrian ﬂows.Optimization of traﬃc conditions is assumed by the device of integrated transport schemes. The main disadvantage of solving this issue is the limited regulatory documentation that would be applicable in urban environments.Materials and methods. In the article, the authors used, as a fundamental method of analogy, a comparison of the categories of streets and urban roads with suburban highways. Also, the advantages of individual road junctions and their systems and the level of convenience of the streets of Tiumen were analyzed.Results. The results are variants of complex traﬃc intersections that satisfy the requirements deﬁned in advance regarding various types of intersections with the following indicators: distance between minor streets, number of lanes on the streets, radii of circular curves.Conclusion. Based on the results of this article, it is advisable to consider the third variant of the complex intersection, which is the most promising in terms of the considered parameters.